Synthesis of quinoline based molecular probes for detection of nitric oxide. (May 2022) - Kaushik, Deepender; Kaur, Manpreet; Mutreja, Vishal; Pathania, Khushboo; Salunke, Deepak B.; Sahoo, Subash Chandra; Saini, Vaneet; Pawar, Sandip V.; Kansal, Sushil K.; Mehta, Surinder K.
Abstract: Nitric oxide (NO), an important signaling molecule of the immune, vascular and nervous system was found to be present in different concentrations in biological fluids such as blood and plasma as well as in neural tissue and endothelium. A variety of competent probes may be required to detect NO and understand its complicated biochemistry, and establish the correlation of its concentrations among different biological media to its biological effect. In order to find new probes as NO sensors, four quinoline-derived ortho -diamines were synthesized and their structures and purities were confirmed by various spectroscopic methods including single-crystal X-ray diffraction. The molecules were investigated for the bimodal sensing (UV–visible and fluorescence) potential for NO. All the probes have showcased both UV–visible and fluorescent signals towards the presence of NO due to the formation of corresponding triazoles. Interestingly, the limit of detection was observed in the nanomolar range (56.1–95 nM) for the four ligands using colorimetric signals. Among the prepared molecules, the N 4 -(4-chlorobenzyl)quinoline-3, 4-diamine exhibited superior sensing parameters viz the limit of detection (LOD), formation constant (Kf ), and quenching constant (Ksv ). An isolated triazole further confirmed the proposed mechanism of NO detection. Graphical abstract: Image 1 Highlights: Quinoline-derived ligands was synthesized and employed for the detection of NO. All the ligands shown bimodal (colorimetric and fluorometric) signals towards NO. N 4 -(4-chlorobenzyl)quinoline-3, 4-diamine exhibited figures of merit.